Comparative appraisal of nutrient recovery, bio-crude, and bio-hydrogen production using Coelestrella sp. in a closed-loop biorefinery - Kopperi, Harishankar; Mohan, S. Venkata (Frontiers in Bioengineering and Biotechnology, 2022)
Graphical Abstract